Passive acoustic localisation of undersea gas seeps using beamforming. (June 2021) - Li, Jianghui; White, Paul R.; Bull, Jonathan M.; Leighton, Timothy G.; Roche, Ben; Davis, John W.
Highlights: This paper has demonstrated the utility of beamforming as a tool for analysis of acoustic data from gas releases. It has shown that the MVDR beamformer offers worthwhile performance gains over CBF in terms of greater enhancement of SNR and in terms of localisation accuracy. Using beamforming it was possible to enhance the SNR and in so doing extend the range over which the passive acoustic system can detect and monitor a gas leak. Abstract: Passive acoustics has been identified as an important strategy to determine underwater gas flux at natural sites, or at locations related to anthropogenic activities. The ability of an acoustic system to detect, quantify and locate a gas leak is fundamentally controlled by the Signal to Noise Ratio (SNR) of the bubble sounds relative to the ambient noise. This work considers the use of beamforming methods to enhance the SNR and so improve the performance of passive acoustic systems. In this work we propose a focused beamforming technique to localise the gas seeps. To achieve high levels of noise reduction an adaptive beamformer is employed, specifically the minimum variance distortionless response (MVDR) beamformer. The technique is demonstrated using an array of five hydrophones collecting data at the controlled CO2 gas release experiment conducted as part of STEMM-CCS (Strategies for Environmental Monitoring of Marine Carbon Capture and Storage) project. The experimental results show that the adaptive beamformer outperforms the conventional (delay and sum) beamformer in undersea bubble localisation. Furthermore, the results with a pair of hydrophone arrays show an improvement of the localisation compared to the use of one hydrophone array.